Modelling the morphological response of the Oka estuary (SE Bay of Biscay) to climate change. (5th December 2022) - Garnier, Roland; Townend, Ian; Monge-Ganuzas, Manu; de Santiago, Iñaki; Liria, Pedro; Abalia, Aritz; Epelde, Irati; Campo, Andrea del; Chust, Guillem; Valle, Mireia; González, Manuel; Mader, Julien; et al.
Abstract: Adaptation in and around estuaries, to ensure the future resilience of both the natural environment and the communities that are located alongside is an increasingly pressing need. As part of an adaptation planning program for the Basque estuaries (northern Spain, south-eastern Bay of Biscay), a modelling system to simulate the morphological response of the Oka estuary to climate change has been developed. Existing knowledge was used as the basis to frame this pilot modelling examining both the short-term change (storm, seasonal, annual) and the longer-term changes (decades to eons). In this paper, we focus on the long-term response and consideration of the output from the process model is limited to the data that was extracted to help parameterize the long-term model. The latter was then used to examine the response of the estuary to the past changes over a historical time scale, where observations from foraminiferal analysis and saltmarsh response were used to establish the predictive validity of the model. Forcing the model with a linear rate of sea level rise representative of the 20th century, the estuary keeps pace with sea level rise in agreement with the observations. An 18.6-year periodic variability was identified over the saltmarshes, by including the effect of the nodal tide, with the last deposition maximum occurring in 2020. The effect of the opening of a saltmarsh that was drained at the beginning of the 18th century was investigated using a simplified schematization and showed sedimentation rates of up to one order of magnitude larger than in natural marsh, in general agreement with the rates obtained in previous studies. To predict the future response of the estuary, simulations with an exponential sea level rise were performed using scenarios obtained from the latest IPCC projections. The estuary fails to keep pace with sea level rise in any of the scenarios considered. The attendant increase in the hydroperiod over the saltmarshes is also likely impact to saltmarsh species productivity and distribution. Despite the simplifications inherent to the model, and the simplifications made in the representation of the estuary and forcing conditions, the methods presented here provide additional insights into long-term behaviour that complement information obtained from more detailed, but short-term, process models. The combined modelling approach allows adaptation measures to climate change to be considered over longer timescales. Highlights: Adaptation to climate change is a problem faced by estuaries around the world. An approach to study adaptation options for the Basque coast (Spain) is proposed. With a linear rate of sea level rise, the Oka estuary keeps pace with sea level rise. The Oka estuary fails to keep pace with future projections of sea level rise. Saltmarsh enclosure and re-opening change the morphological response of the estuary.